How to evaluate libraries’ sustainability? An approach to an evaluation model and indicators - Karioja, Elina (BIBLIOPOLIS, 2020)
This paper originated from conclusions I wrote down in doing my thesis about sustainability in libraries. At first it is necessary to understand library’s recycling role in society and its sustainable development in basic functions like borrowing and returning books or offering open and free space to the public. Environmental certifications like LEED or environmental management systems (ISO 14000) are not fully compatible with libraries and they lack the understanding of special features of libraries. Oulu University of Applied Sciences is planning a project in order to meet this need and creating an evaluation model and indicators of sustainable development for libraries. Sustainable areas taken into consideration in evaluating library’s sustainability could be space, green IT, strategies, collection management, location and environmental awareness of both public and staff. It is also noteworthy to consider different levels of analysis: users, library staff, decision makers and host organization. Users should be offered recycling points for books and waste, staff should be committed to sustainability and communicate their awareness. Library strategies should include a sustainable point of view. It is noteworthy that the library is often a part of a large organization in a municipality, town or school, college, university etc. If the host organization has an environmental management system, library is most likely a part of that. In cases where there is no environmental policy in a host organization, it is much more difficult to follow one. Sustainability needs commitment from every person in the organization. As a result of this project, a specific libraries’ environmental label and auditing system could be developed which would increase environmental awareness among staff and customers and would make libraries greener, more sustainable, which is the ultimate objective. One can optimistically state that this model could be used worldwide and this project made international from the very beginning.